A traversodontid cynodont of African affinity in the South American Triassic - Abdala, F; Sa-Teixeira, AM (Bernard Price Institute for Palaeontological Research, 2004)
Traversodontidae represent one of the most diverse and abundant families of non-mammaliaform cynodonts, particularly in Gondwanan faunas of Middle to Late Triassic age. Although a great diversity of traversodontids is known for South American (approximately nine species) andAfrican (six to seven species) Triassic faunas, the record of the group in these continents does not show similarities beyond the family level. Here we describe a new traversodontid, Luangwa sudamericana, from the Santa Maria Formation of southern Brazil, which is most similar to the Anisian traversodontids Luangwa drysdalli from the upper portion of the Ntawere Formation in Zambia, and Scalenodon angustifrons from the Manda Formation in Tanzania. Features in common with these African taxa are oval-outlined upper postcanines presenting an anterior labial cingulum. The new species is similar to L. drysdalli in a number of features, including the presence of a posterior cingulum in the upper postcanines, anterior cingulum in front of the transverse crest in the lower postcanines, short snout, enormous orbits and short temporal region. Differences with L. drysdalli are the less developed posterior cingulum behind the upper transverse crest that does not extend along the entire posterior border of the tooth, and the presence of a well-defined posterior accessory cusp on the sectorial crest of the upper postcanines. The comparison of the quadrate, preserved in situ in the squamosal notch of the new taxon, and that from other traversodontids, suggests that the quadratojugal is involved in the formation of the lateral condyle of the traversodontid suspensorium. Luangwa represents the first genus of traversodontid, and the second of non-mammaliaform cynodont shared by South American and African faunas. A significant biochronological implication of this finding is that part of the Santa Maria Formation may now be considered Anisian in age, and thus older than generally recognized for the unit.
Keywords: Traversodontidae, Middle Triassic, Brazil, Zambia, Cynodontia, Luangwa